Comparison of 3D-navigation and fluoroscopic guidance in percutaneous pedicle screw placement for traumatic fractures of the thoracolumbar junction - Fenna Brunken; Eric Mandelka; Benno Bullert; Paul Alfred Gruetzner; Sven Y. Vetter; Jula Gierse (Brain and Spine, 2024)
Introduction: Fractures of the thoracolumbar junction are the most common vertebral fractures and can require surgical treatment. Several studies have shown that the accuracy of pedicle screw placement can be improved by the use of 3D-navigation. Still only few studies have focused on the use of navigation in traumatic spine injuries. Research question: The aim of this study was to compare the screw placement accuracy and radiation exposure for 3D-navigated and fluoroscopy-guided percutaneous pedicle screw placement in traumatic fractures of the thoracolumbar junction. Materials and methods: In this single-center study 25 patients undergoing 3D-navigated percutaneous pedicle screw placement for traumatic fractures of the thoracolumbar junction (T12-L2) were compared to a control group of 25 patients using fluoroscopy. Screw accuracy was determined in postoperative CT-scans using the Gertzbein-Robbins classification system. Additionally, duration of surgery, dose area product, fluoroscopy time and intraoperative complications were compared between the groups. Results: The accuracy of 3D-navigated percutaneous pedicle screw placement was 92.66 % while an accuracy of 88.08 % was achieved using standard fluoroscopy (p = 0.19). The fluoroscopy time was significantly less in the navigation group compared to the control group (p = 0.0002). There were no significant differences in radiation exposure, duration of surgery or intraoperative complications between the groups. Discussion and conclusion: The results suggest that 3D-navigation facilitates higher accuracy in percutaneous pedicle screw placement of traumatic fractures of the thoracolumbar junction, although limitations should be considered. In this study 3D-navigation did not increase fluoroscopy time, while radiation exposure and surgery time were comparable.